2021
DOI: 10.1002/nano.202000249
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress toward highly efficient tin‐based perovskite (ASnX3) solar cells

Abstract: Recently, lead halide perovskites have attracted great attention in photovoltaic field because of high power conversion efficiency. However, the toxicity of lead in perovskite can result in environment issues, which are the major challenge for commercial application. In this context, environmentally friendly lead‐free perovskite alternatives are highly desired. Bearing excellent photophysical and electronic properties, tin‐perovskites (ASnX3) are the most promising alternative. In reality, extensive efforts ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 204 publications
(264 reference statements)
0
16
0
1
Order By: Relevance
“…The fast crystallization makes it tricky to precisely control the film morphology and to achieve smooth, uniform, and pinhole‐free films, being detrimental to the device performance. [ 109 ] With the aid of in situ GIWAXS characterizations, the underlying crystallization mechanisms of tin‐based perovskites were also investigated, providing insights for the control of the film formation process. For instance, Portale et al.…”
Section: Crystallization Kinetics Of Lead‐free Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fast crystallization makes it tricky to precisely control the film morphology and to achieve smooth, uniform, and pinhole‐free films, being detrimental to the device performance. [ 109 ] With the aid of in situ GIWAXS characterizations, the underlying crystallization mechanisms of tin‐based perovskites were also investigated, providing insights for the control of the film formation process. For instance, Portale et al.…”
Section: Crystallization Kinetics Of Lead‐free Perovskitesmentioning
confidence: 99%
“…The fast crystallization makes it tricky to precisely control the film morphology and to achieve smooth, uniform, and pinhole-free films, being detrimental to the device performance. [109] With the aid of in situ GIWAXS characterizations, the underlying crystallization mechanisms of tin-based perovskites were also investigated, providing insights for the control of the film formation process. For instance, Portale et al analyzed the crystallization kinetics of FASnI 3 by in situ GIWAXS, and observed a direct phase transition from the disordered precursors to FASnI 3 perovskite crystals at room temperature (Figure 23a,b), without the formation of any intermediate or complex phases.…”
Section: Crystallization Kinetics Of Lead-free Perovskitesmentioning
confidence: 99%
“…The reason for this inference is that the migration as well as the accumulation of ions can change the intrinsic electric field of the perovskite films, even causing local crystal structure changes, which in turn lead to further degradation of the PSCs and severely affect the operating stability. [15,16] Apart from these, ion migration can also cause slow photoconductivity response, halide redistribution, and segregation. [17] In order to push the commercialization step of PSCs, a clear understanding of the ion migration in OIHPs is meaningful and highly desired.…”
mentioning
confidence: 99%
“…They can precisely inactivate the surface and stabilize the ABX 3 phase. [ 95 ] DFT calculations indicated a declining tendency from F, Cl, Br for SnX 2 ; thereby, it was accepted inactivating the surface and GB and thus enhancing the stability of B‐γ‐CsSnI 3 ( Figure ). [ 141 ] It is widely acknowledged that the stability of CsSnI 3 layer relied strongly on the concentration of vacancies and GBs.…”
Section: Materials Synthesis and Device Optimizationmentioning
confidence: 99%
“…The emerging layer is smooth with bigger grains and reduces unwanted recombination, thereby giving excellent PV performance. [ 95 ] Successive deposition of SnBr 2 and MABr was exploited to eliminate the exposure of Sn 2+ throughout the formation of lead‐free PSC. After reaction, annealing at 150°C in glove box was performed; finally, MASnBr 3 layers were obtained with excellent crystallinity and reduced oxidation.…”
Section: Materials Synthesis and Device Optimizationmentioning
confidence: 99%